1996
DOI: 10.1063/1.115706
|View full text |Cite
|
Sign up to set email alerts
|

Role of C and B clusters in transient diffusion of B in silicon

Abstract: Transient diffusion of ion-implanted B is inhibited in the presence of high C or B concentrations, due to the formation of interstitial clusters stabilized by impurity atoms. Comparison between experiments and simulations suggests that the number of self-interstitials trapped per clustered impurity atoms is Ϸ1.15 for C and ϳ1 for B, consistent with a volume compensation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 6 publications
2
26
0
Order By: Relevance
“…As mentioned in the introduction, the interest in the behavior of carbon in silicon increased drastically when it was shown that a high concentration of grown-in carbon almost suppressed TED of boron [11,12]. Initially, it was assumed that substitutional carbon would simply trap silicon self-interstitials and thus reduce their concentration.…”
Section: Behavior Of Grown-in Carbon At High Concentrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned in the introduction, the interest in the behavior of carbon in silicon increased drastically when it was shown that a high concentration of grown-in carbon almost suppressed TED of boron [11,12]. Initially, it was assumed that substitutional carbon would simply trap silicon self-interstitials and thus reduce their concentration.…”
Section: Behavior Of Grown-in Carbon At High Concentrationsmentioning
confidence: 99%
“…The fact that implanted carbon does not lead to interstitial-type dislocation loops [4] indicates that carbon atoms somehow 're-absorb' the produced self-interstitials. The additional observation that carbon implantation may even reduce TED of boron indicates that carbon may capture back more than just the one extra self-interstitial generated, but roughly ten to fifteen percent more, if the actual results are taken into account [12]. In analogy to the popular "+1 model" one could speak of a "minus 0.1 model" in the case of carbon implantation.…”
Section: Precipitation Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…73 Further confirmation of this came with the evidence that B clustering effectively contributes to lower the I supersaturation following ion implantation. 74 In addition, a proper substitutional B concentration was demonstrated to suppress the typical {311} defects, by a competitive BIC formation. 75 The phenomenon of B-I clustering has a clear negative drawback as far as the dopant activation is concerned, but in addition, it has a weighty effect on the B diffusion process and on its simulation.…”
Section: B-i Clusters Formation and Dissolutionmentioning
confidence: 99%
“…[7][8][9] Nonequilibrium B diffusion and BIC formation have been the subject of many studies to control and suppress them. Different approaches have been proposed, [10][11][12][13][14] but a method suitable for both c-Si and PA-Si, that is also easily implemented in industrial Si-based device production, is still lacking.…”
Section: Introductionmentioning
confidence: 99%